What Nurses Should Know About New Ways to Treat Muscle Pain - V. Basil Hans (International Journal of Orthopedic Nursing and Practices, 2025)
Muscle discomfort is a common clinical concern that can significantly limit mobility, functional ability, and overall quality of life. Recent advancements in assessment and management strategies have enabled nurses to deliver more precise, evidence-based care for patients experiencing muscular pain. Emerging diagnostic approaches now include enhanced screening scales that offer greater sensitivity in identifying pain patterns, as well as digital monitoring tools that allow continuous evaluation of symptoms across care settings. These innovations support earlier detection and more accurate characterization of muscle-related discomfort. Pharmacological management has also evolved, with renewed focus on the safe and effective use of NSAIDs, muscle relaxants, and adjunct therapies. Updated prescribing practices emphasize minimizing side effects, optimizing dosing, and integrating medication choices with individual patient needs. Alongside drug therapy, non-pharmacological interventions continue to expand, offering valuable alternatives or complements to medication. Therapeutic exercise, heat and cold applications, manual therapy techniques, and mind–body practices such as relaxation training and guided breathing have demonstrated benefits in reducing muscle tension and improving functional outcomes. Current best practices highlight the importance of personalized care planning that considers a patient’s unique symptoms, lifestyle, and treatment goals. Early intervention and interdisciplinary collaboration—particularly among nurses, physical therapists, physicians, and pain specialists—enhance the effectiveness of treatment strategies and support holistic recovery. By staying informed about these evolving trends, nurses are well-positioned to reduce muscle discomfort, improve patient comfort, and promote faster functional rehabilitation across diverse healthcare environments.
Keywords: Muscle discomfort; non-pharmacological interventions; pain assessment; personalized care planning; pharmacological management